IMPLIKASI HUKUM TERHADAP AKAD YANG MEMUAT KLAUSUL PENYELESAIAN SENGKETA PERBANKAN SYARIAH MELALUI PENGADILAN NEGERI PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 93/PUU-X/2012 - Hasima, Rahman (Faculty of Law, Universitas Pattimura, 2020)
This research aims to determine the legal implications of the agreement on which the sharia banking dispute resolution clause was submitted through the state court's post-decision of the Constitutional Court No. 93/PUU-X/2012. The research method used normative research with a statute approach and a conceptual approach and analyzed descriptive qualitative. The results of the study show that the contract that contains the clause for the settlement of Islamic banking disputes through the District Court after the Constitutional Court decision has the implication of being null and void because it contradicts the contract or causa that is lawful, so that the parties make an addendum so that no future disputes occur.